Impacts of soft soil compaction and groundwater extraction on subsidence in the Yellow River Delta. Issue 12 (2nd December 2021) - Zhang, Yi; Huang, Haijun; Liu, Yanxia; Bi, Haibo; Zhang, Zehua; Wang, Kuifeng; Yan, Liwen
Abstract: Recently, many of the world's major river deltas have been sinking, making them increasingly vulnerable to floods and storm surges, salinization and permanent inundation. For the Yellow River delta, annual subsidence rates of several to dozens of centimeters have been reported in the past few years. The extraction of a considerable amount of groundwater due to continuous pumping is suggested as the main driver of the groundwater depression cone. Despite its scale and severity, methods to quantify subsidence are scarce. We introduce a soil mechanics approach to quantify subsidence due to the compaction of soft soil. The largest reduction in soft soil thickness, which is more than 2.6 m, occurred in the salt field area to the north of the Yellow River. Furthermore, by estimating the primary consolidation of soft soil, the subsidence caused by groundwater exploitation is quantified. In the coastal area of the delta, due to excessive exploitation of shallow underground brine resources, the maximum accumulated subsidence is as high as 2 m. Since the natural consolidation of these deltaic sediments has ended, if the current groundwater exploitation intensity is maintained, major subsidence disasters, such as subsidence depressions and ground fissures, will occur.